Spatial Differentiation of Social Development in Poland. Analysis on Nuts 3 Level - Laskowska, Iwona; Dańska-Borsiak, Barbara (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
Regional development occupies an important place in the policy of the European Union. One of its priorities is to equalize the differences in the level of development of regions assessed more broadly than just the economic dimension. Broad understanding of regional development takes into account its social dimension. To assess the socio‑economic development at the national level, a synthetic indicator called the Human Development Index (HDI) is commonly used. However, HDI values do not describe the inequalities that exist between regions within countries. The main aim of this study is to assess the level of social development in regional (NUTS 3) perspective in Poland using the Local Human Development Index (LHDI) and to attempt to identify the determinants of social development at the local level. The way of constructing LHDI was proposed by the UNDP Project Office in Poland and was only slightly modified for the purposes of this study. The analysis of social development at the local level is important because it can serve as a tool for understanding the causes of existing and future social problems. Another important goal of the research is the analysis of the spatial relationship of social development, which allows to determine whether the strong regions, being local economic centres positively influence the development of the neighbouring regions.